2022
DOI: 10.3390/su14042015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Regulation on Green Total Factor Productivity: An Evidence from the Yellow River Basin, China

Abstract: Based on the data of 59 prefecture-level cities in the Yellow River Basin from 2011 to 2019, this paper uses the Slack Based Measure-Global Malmquist Luenberger (SBM-GML) model to measure green total factor productivity (GTFP) of the cities. Under the space–time concept of the Basin, heterogeneity analysis of the upper, middle and lower reaches of the Yellow River Basin is conducted. On this basis, a panel Tobit model is constructed to analyze the impact of environmental regulation on GTFP in the whole basin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…From the perspective of cities, Fan et al [23] found that the innovation level of green technology promoted the development of green economy in Chinese cities, and this conclusion was also verified in the development of Italian cities [24]. Mao et al [25] studied cities in the Yellow River basin using the tobit model and found that green technology progress drove the increase of green total factor productivity in the whole region, but the upward trend of each basin is different, and this conclusion is also applicable to the Yangtze River basin [26]. Based on the analysis of China's carbon emission trading policy, Huang and Huang [27] found that the implementation of this policy promoted the green total factor productivity of pilot cities, which was mainly achieved by low-carbon innovation.…”
Section: Literature Review and Influencing Mechanism Analysismentioning
confidence: 92%
“…From the perspective of cities, Fan et al [23] found that the innovation level of green technology promoted the development of green economy in Chinese cities, and this conclusion was also verified in the development of Italian cities [24]. Mao et al [25] studied cities in the Yellow River basin using the tobit model and found that green technology progress drove the increase of green total factor productivity in the whole region, but the upward trend of each basin is different, and this conclusion is also applicable to the Yangtze River basin [26]. Based on the analysis of China's carbon emission trading policy, Huang and Huang [27] found that the implementation of this policy promoted the green total factor productivity of pilot cities, which was mainly achieved by low-carbon innovation.…”
Section: Literature Review and Influencing Mechanism Analysismentioning
confidence: 92%
“…The HQAD level value, used as explanatory variable, has the characteristics of nonnegative truncation, ranging between 0 and 1 (Table 5). This paper, therefore, uses panel Tobit regression for driving factor analysis to avoid biased estimates of the restricted explanatory variables under the OLS method [45,46]. The following analytical model was constructed.…”
Section: Methodsmentioning
confidence: 99%
“…Banking and finance play fundamental roles in public policy and economic performance, as well as in all forms of commerce and industry, and adequate financial support is also essential for the sustainable development of society [14]. As far as we know, the term "green credit" mainly appears in research related to China.…”
Section: Literature Reviewmentioning
confidence: 99%